Statistical Estimation of Private Sector Groups Included in the Social Security System in Syria Assistant Professor (Damascus University Journal for the economic and Political sciences, 2024)
This statistical study that deals with the financial situation of the private sector fund in the Syrian social security system is one of the crucial pillars of the basic financial system for social insurance, although there is great difficulty in separating the private sector from the public sector, given that the contributions of these two sectors flow into one fund. Therefore we will try to separate them by simulating a virtual fund within the Social Insurance Institution so that we can apply scientific statistical methods to the private sector without looking at the public sector. Therefore, we have adopted in this study the provisions that take into account the benefits, contributions and individual data of those covered, including contributors, pensioners, death cases, end-of-service compensation information, in addition to the audited annual financial statements for the years 2006-2010 and the annual reports issued by the corporation in the years 2005-2010. Which led us to draw up demographic and other financial estimates and estimate any benefits for members of the private social insurance fund. The estimates were made for a period of 25 years, so the last year of assessment is 2035, and these estimates will mainly contribute to determining the numbers of males and females separately and for the purpose of estimating income and expenditures in the private sector fund, which comprises estimates of the salaries of the participants in the future as well as the possibilities presented for their entitlement to some benefits, which include: old-age pension, disability pension (natural and related to work), beneficiaries’ pensions, pensioners, family compensation and installment payments such as end-of-service compensation, grants for marriage and death, and others.
Keywords: Social Security; Compulsory Insurance Coverage; Pensions for the Covered; Benefit s Estimates